ANALISIS PENERAPAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KEUANGAN PADA BADAN KEUANGAN DAN ASET DAERAH KABUPATEN MALUKU TENGGARA - Rahantoknam, Trivena Anastasia; Tinangon, Jantje J.; Mawikere, Lidia M. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Financial SIMDA is an application program that is shown to assist Local Government in the area of financial management. The purpose of the implementation of financial SIMDA is to produce financial statements and financial information in a timely, complete, accurate, and reliable manner in accordance with the prevailing provisions and encourage the realization of Good Governance and the implementation of regional financial management based on information technology. The purpose of this research is to analyze the implementation of Financial SIMDA in BKAD of Southeast Maluku Regency. The research method used is descriptive qualitative. The results of the research indicate that in general the staff of BKAD of Southeast Maluku Regency have understood the meaning of financial SIMDA. Factors that have to support implementation of SIMDA financial implementation that is communication, attitude / disposition and bureaucracy structure. Meanwhile, the inhibiting factor is human resources. The quality of information generated by financial SIMDA can be understood, relevant, reliable, and comparable.Keywords : Financial SIMDA,ImpplementationÂ SIMDA